LOW EXCLUSIVE BREAST MILK IN BABIES AGED 0-6 MONTHS - Anggi Lestari; Marniati Marniati; Sufyan Anwar; Maiza Duana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Knowledge and culture have an important role in increasing the coverage of exclusive breastfeeding for infants aged 0-6 months. Based on the results of the survey directly obtained in the field, the coverage of exclusive breastfeeding for infants aged 0-6 months is low. The purpose of this study was to examine the low coverage of exclusive breastfeeding in the working area of the Meutulang Health Center, Panton Reu District, West Aceh Regency. The research method used is a qualitative method with an exploratory descriptive approach, namely conducting in-depth interviews, which aims to explore the reasons why mothers do not exclusively breastfeed their babies until the age of 6 months. The results showed that the knowledge of breastfeeding mothers was still lacking regarding understanding in exclusive breastfeeding, the attitude of breastfeeding mothers was still not sure about giving only breast milk. culture is very closely related to exclusive breastfeeding, where mothers hold on to ancestral cultures that are passed down from generation to generation such as the peucicap culture and the provision of complementary feeding is given to infants before the age of 6 months, which should only be given breast milk. The conclusion is that exclusive breastfeeding in the working area of the Meutulang Public Health Center is still low, as evidenced by the results of research that has been carried out where knowledge and culture have a strong influence which is then followed by the attitude and work of the mother. Suggestions are expected for health centers and related agencies to more often conduct counseling, outreach and education to the community, especially mothers about the importance of exclusive breastfeeding aged 0-6 months